The Impact of ERP and IoT Technologies on Improving Operational Sustainability in the Logistics Sector in Surabaya - Farida Arinie Soelistianto; Heri Setiyawan (West Science Interdisciplinary Studies, 2026)
The logistics sector plays a critical role in supporting economic growth and supply chain efficiency, while simultaneously facing increasing pressure to adopt sustainable operational practices. Digital transformation technologies, particularly Enterprise Resource Planning (ERP) and the Internet of Things (IoT), have emerged as important tools for enhancing operational sustainability through improved resource management, real-time monitoring, and process optimization. This study aims to analyze the impact of ERP and IoT technologies on operational sustainability in the logistics sector in Surabaya. A quantitative research approach was employed using a survey method involving 100 respondents from logistics companies operating in Surabaya. Data were collected through structured questionnaires measured using a five-point Likert scale and analyzed using SPSS Version 25. The analytical techniques included validity and reliability testing, descriptive statistics, classical assumption testing, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing. The results reveal that ERP technology has a positive and significant effect on operational sustainability. Similarly, IoT technology significantly influences operational sustainability. Simultaneously, ERP and IoT technologies significantly affect operational sustainability, explaining 53.9% of the variance in operational sustainability. These findings indicate that the integration of ERP and IoT technologies enhances operational efficiency, resource utilization, process optimization, and organizational resilience, thereby contributing to sustainable logistics operations. The study highlights the strategic importance of digital transformation in supporting long-term sustainability and competitiveness within the logistics sector.